Catalytic combustion of coke nuts and in-situ NO reduction under the action of steel scale. (1st April 2021) - Lei, Zhiping; liu, Meichen; Yan, Jingchong; Chun, Tiejun; Fang, Jia; Li, Zhanku; Shui, Hengfu; Ren, Shibiao; Wang, Zhicai; Cao, Xianzhong; Kong, Ying; Kang, Shigang
Highlights: Steel scale exhibited better catalytic effects on coke nuts combustion. 6% steel scale results in 31.4% NO reduction during coke nuts combustion. 6% steel scale modified coke nuts can reduce NO by 18% during the micro-sintering process. Fe3 O4 and Fe2 O3 are the major components that play a catalytic role in steel scale. Abstract: Cheap, efficient and easily available catalysts are key factors for the industrial application of catalytic combustion of coal or coke. The coexistence of Fe with different valences makes the steel scale (SS) promising catalysts for coal/char combustion and in-situ reduction of NO emission. The feasibility of catalytic coke combustion and in-situ reduction of NO emission during combustion by SS was investigated in this paper. Thermogravimetric analysis validated that the addition of 6% SS resulted in the decrease of both burnout temperature and burnout time, increase of combustion and burnout index of coke nuts by 1.17 and 1.50 times, respectively, and the NO emission was reduced by 31.4%. Micro-sintering experiments demonstrated that NO emission could be reduced by 18% by using SS-modified coke nuts as fuel. Fe3 O4 and Fe2 O3 were proved as the dominant components responsible for the catalysis of SS. These results verify that SS has great potential in catalytic combustion of coke nuts and in-situ NO reduction during the iron ore sintering process.